A Genre-Based Approach to Improve The Students’ Writing Skills - Fikry Aji Wicaksono; Sulistyaningsih Sulistyaningsih; Abd. Syakur (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to describe the improvements of the ninth-grade students at MTs Unggulan Al-Jadid. This was an action research study with two cycles, and the research procedures were planning, action and observation, and reflection. The students from class 9-E at MTs Unggulan Al-Jadid in the academic year 2020/2021, with a total of 25 students chosen through a purposive sampling technique, and an English teacher, were the participants. The instruments were a field note and a test. The results revealed that the mean pre-test score was only 60.25 (pre-test), but it improved significantly from cycle I to cycle II (from 72.50 to 80.25). To highlight, at the beginning of this study (pre-research), the highest score was 70, and by the end of the study, it had improved to 78-92. Meanwhile, the participants with the lowest scores improved significantly on the post-test compared to the pre-test. The pre-test score ranged from 50 to 70, while the post-test score ranged from 70 to 74.